2010
DOI: 10.1590/s1516-35982010000400021
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance and composition of milk protein fraction in dairy cows supplemented with fat sources

Abstract: -The objective of this study was to evaluate the use of fat sources in rations for lactating cows on the productive performance and composition of milk protein fraction. Twelve Holstein cows were used, grouped in three balanced 4 × 4 Latin squares, fed with the following rations: control; refined soybean oil; whole raw soybean; and calcium salts of unsaturated fatty acid (Megalac-E). Dry matter and nutrient intake, and daily milk production were evaluated. The samples used to analyze milk composition were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…The results for casein content found in this study are similar to the levels reported by Bateman et al (1999). Concentrations of milk true protein, and casein, as expressed in %CP, are in accordance to the values reported by Coulon et al (1998) andFreitas Jr. et al (2010).…”
Section: Resultssupporting
confidence: 92%
“…The results for casein content found in this study are similar to the levels reported by Bateman et al (1999). Concentrations of milk true protein, and casein, as expressed in %CP, are in accordance to the values reported by Coulon et al (1998) andFreitas Jr. et al (2010).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, we believe that the quality of the pasture provided a satisfactory intake of nutrients, which met the requirements of the animals when associated with the forage, thus fulfilling the requirements for their milk production levels. Freitas Júnior et al (2010) did not find any effects on the corrected milk production when using different sources of lipids in the diet of lactating cows with 55.0 g/kg of EE in the dietary dry matter. According to the results of Borba et al (2006), Freitas Júnior et al (2010, and the present work, levels of up to 80 g/kg of EE in the diet do not interfere with the production, and the producer may opt for the diet that is most economic.…”
Section: Discussionmentioning
confidence: 83%
“…Freitas Júnior et al (2010) did not find any effects on the corrected milk production when using different sources of lipids in the diet of lactating cows with 55.0 g/kg of EE in the dietary dry matter. According to the results of Borba et al (2006), Freitas Júnior et al (2010, and the present work, levels of up to 80 g/kg of EE in the diet do not interfere with the production, and the producer may opt for the diet that is most economic. Costa et al (2007) reported increased corrected milk production when using diets with 50.0 g/kg of EE containing protected oil, whole rice meal plus rice oil, and whole rice meal plus bovine tallow as sources of lipids.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations